Political Interference in Higher Education Quality Assurance. The Swedish Case - Adamson, Lena (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2016)
This paper presents the Swedish national Quality Assurance system for Higher Education introduced in 2011. The system was created by officials at the Ministry of Education and introduced by the Government in spite of a) widespread criticism from the Swedish Higher Education sector, students, national and international expertise, and b) the existence of a well accepted proposal for a new system created by the Higher Education Agency in collaboration with academia and students. The system caused Sweden to be excluded from the European Association for Quality Assurance in Higher Education (ENQA). The article reflects on the need for organisations as ENQA not only to guarantee quality but also to guard the border between the Higher Education Institutions and the political powers.